Predictors of outcome in 1-month survivors of large middle cerebral artery infarcts treated by decompressive hemicraniectomy. Issue 5 (12th March 2020) - Casolla, Barbara; Kyheng, Maeva; Kuchcinski, Gregory; Lejeune, Jean-Paul; Hanafi, Riyad; Bodenant, Marie; Leys, Didier; Labreuche, Julien; Allart, Etienne; Jourdain, Merce; Cordonnier, Charlotte; Henon, Hilde
Abstract : Background: Decompressive hemicraniectomy (DH) increases survival without severe dependency in patients with large middle cerebral artery (LMCA) infarcts. The objective was to identify predictors of 1-year outcome after DH for LMCA infarct. Methods: We conducted this study in consecutive patients who underwent DH for LMCA infarcts, in a tertiary stroke centre. Using multivariable logistic regression analyses, we evaluated predictors of (1) 30-day mortality and (2) poor outcome after 1 year (defined as a modified Rankin Scale score of 4–6) in 30-day survivors. Results: Of 212 patients (133 men, 63%; median age 51 years), 35 (16.5%) died within 30 days. Independent predictors of mortality were infarct volume before DH (OR 1.10 per 10 mL increase, 95% CI 1.04 to 1.16), delay between symptom onset and DH (OR 0.41, 95% CI 0.23 to 0.73 per 12 hours increase) and midline shift after DH (OR 2.59, 95% CI 1.09 to 6.14). The optimal infarct volume cut-off to predict death was 210 mL or more. Among the 177 survivors, 77 (43.5%) had a poor outcome at 1 year. Independent predictors of poor outcome were age (OR 1.08 per 1 year increase, 95% CI 1.03 to 1.12) and weekly alcohol consumption of 300 g or more (OR 5.30, 95% CI 2.20 to 12.76), but not infarct volume. Conclusion: In patients with LMCA infarcts treated by DH, stroke characteristics (infarct volume before DH, midline shift after DH and early DH) predict 30-day mortality, while patients' characteristics (age and excessive alcohol intake) predict 1-year outcome survivors.